Własności Materiałów przy Gięciu Walcowym - Klepaczko, J.; Litoński, J. (Engineering Transactions, 1961)
Experimental curves are presented for bending of sheet aluminium, brass and steel of several types. The knowledge of these curves enables a simple determination of forces, moments and strain work and also the form of the bent element and other quantities connected with bending processes, [1]. For a given material, these curves represent the relation between the ratio of the bending moment to the section index and the ratio of the half-thickness of the sheet metal to the curvature radius and the relation between the ratio of the area below this curve to the area of the rectangle with sides M/W and g/o, where M denotes the bending moment, w the section modulus, g the thickness, g radius of curvature and the ratio of the half-thickness to the curvature radius. Two test methods were used. In the first, the test-piece (of sheet metal) was loaded with the bending moment in a special device, in the second it was bent on about a form block. The bending curves obtained by the first and the second method coincide within the limits of the measurement error.